Minilaparotomy for type II and III radical hysterectomy: technique, feasibility, and complications. Issue 5 (1st August 2004) - Fagotti, A.; Fanfani, F.; Ercoli, A.; Patrizi, L.; Mancuso, S.; Scambia, G.
Abstract : The objective was to assess the feasibility, the operative and postoperative outcome, and complications in the use of minilaparotomy for type II and III radical hysterectomy (RH) and pelvic lymphadenectomy (PLN) in early-stage cervical/endometrial cancer. A pilot study on 91 consecutive patients submitted to type II and III RH and PLN for early-stage cervical/endometrial cancer was performed between March 2002 and May 2003 in the Division of Gynecologic Oncology (UCSC, Rome). Thirty-two of 91 cases (35.2%) were eligible for minilaparotomy. The mean operative time was 156.7 min, whereas the mean intraoperative estimate of blood loss was 303.7 ml. A mean number of 32.7 pelvic lymph nodes and 6.2 common iliac nodes were removed. Ileus and removal of bladder catheter were on mean postoperative day 2.4 and 3.4, respectively. The mean number of postoperative days spent in the hospital was 3.7. Intra- and postoperative parameters were compared to laparotomy controls and literature data on laparoscopy and Pfannenstiel incision, showing substantially comparable results. Minilaparotomy is acceptable for selected patients undergoing radical abdominal hysterectomy (RAH) and PLN and does not compromise the adequacy of the procedure. It can be considered as an alternative to the classic midline vertical incision or even to the Pfannenstiel incisions and laparoscopy.